Characterizing archaeological bronze corrosion products intersecting electrochemical impedance measurements with voltammetry of immobilized particles - Redondo-Marugán, Jorge (2017)
Application of electrochemical impedance measurements to microparticulate deposits of copper corrosion products attached to graphite electrodes in contact with 0.10 M aqueous HClO4 electrolyte is described. The impedance measurements were sensitive to the applied potential and the amount of solid sample and were modeled taking into account the contribution of the uncovered base electrode. Several pairs of circuit elements provide monotonic variations which are able to characterize different corrosion compounds regardless the amount of microparticulate solid on the electrode. Application to a set of archaeological samples from the archaeological Roman site of Gadara (Jordan, 4th century AD) permitted to establish a grouping of such samples suggesting different provenances/manufacturing techniques.